Investigation of Pharmacodynamic and Pharmacokinetic Interactions Between Rivaroxaban and Enoxaparin in Healthy Male Subjects. Issue 3 (15th May 2013) - Kubitza, Dagmar; Becka, Michael; Schwers, Stephan; Voith, Barbara
Abstract Rivaroxaban, an oral, direct factor Xa inhibitor, is currently used in clinical practice for the prevention and treatment of thromboembolic disorders. This single‐center, three‐way crossover study was designed to investigate the pharmacodynamic effects of rivaroxaban (10 mg) and enoxaparin (40 mg) alone and in combination as well as the influence of enoxaparin on the pharmacokinetics of rivaroxaban in healthy male subjects. When given alone, both drugs exhibited similar, rapid anti‐factor Xa activity. Combined administration resulted in an increase of ∼50% in anti‐factor Xa activity and a lesser increase in activated partial thromboplastin time, compared with either drug alone. Enoxaparin had no additional effect on prolongation of the prothrombin time induced by rivaroxaban and did not affect the pharmacokinetic parameters of rivaroxaban. The results showed that rivaroxaban (10 mg) and enoxaparin (40 mg) had a similar and rapid onset of action, as indicated by the similar anti‐factor Xa activity–time curves, suggesting that both drugs have a similar duration of pharmacological activity at the factor X site. Co‐administration of rivaroxaban and enoxaparin is associated with enhanced pharmacodynamic effects.